Optimizing project outcomes through agile methodologies: A case study of «Alfa-Bank» JSC Russia - Ermiychuk, Irina (2025)
The increasing complexity of project management in financial institutions re-quires flexible and adaptive approaches. Agile methodologies have emerged as a popular alternative to traditional project management approaches that help organizations respond effectively to changing business environments. This thesis aims to examine the implementation of Agile methodologies at Alfa-Bank JSC, Russia, and evaluate how they have impacted project efficiency, stakeholder engagement, and organizational performance. This research uses a case study approach to examine Alfa-Bank’s internal reports, financial state-ments, and Agile implementation strategies from 2021 to 2024. The study is supported by a content analysis that provides a theoretical framework for Ag-ile practices in banking. Project performance indicators, financial measures, and organizational changes are compared before and after the adoption of Ag-ile. The results indicate that the Agile approach at Alfa-Bank enhanced project flexibility, improved communication and integration among teams, and in-creased decision-making speed. However, some issues were revealed during the study, including resistance to change, the problem of integration with cur-rent banking regulations, and limited resources. The study is consistent with the findings of previous research that highlights the effectiveness of Agile methodologies in improving project management processes in financial ser-vices organizations and addresses the importance of strategic planning, lead-ership, and organizational flexibility for successful Agile implementation. To this end, this research adds to the existing body of knowledge on Agile project management in banking and provides practice recommendations that can help other financial institutions achieve better project outcomes through Agile ap-proaches. Keywords: Agile project management, Scrum, financial sector, Alfa-Bank, banking innovation.